Time and technique of green pruning ’Charme’ peaches to obtain quality fruits - Dotto, Marcelo; Pirola, Kelli; Cassol, Darcieli Aparecida; Junior, Américo Wagner; Citadin, Idemir; Antunes, Luis Eduardo Correa (Scientia Agraria Paranaensis, 2021)
One of the management techniques that aim to improve the quality of the fruits is green pruning, which main purpose is to increase the penetration of light in the crown, favoring pigmentation, thus improving the flavor of the fruits. However, it is not always done, since it requires labor. The objective of this work was to evaluate the time and the way of Management green pruning, as well as the practice of thinning associated with it in order to obtain high quality peaches from the ‘Charme’ cultivar. The work was carried out in a commercial orchard in the Dois Vizinhos (PR) municipality, in three productive cycles. A completely randomized design was used, a 3 x 3 bifactorial scheme (green pruning time x green pruning management technique), with 4 replications of two plants per experimental unit. The times of green pruning or bending were in the third, fourth and fifth weeks before harvest. The techniques were first to remove vertical branches facing the center of the canopy and in the base of the tree with reference to broken and poorly ones and, the second the belding of these. The productive capacity and the physicochemical characteristics of the fruits were evaluated in three productive cycles. The quality of the ‘Charme’ peach only presented improvements with the green pruning from the third year of its realization.